Utility of stent double palliation for esophageal cancer with airway involvement: the extremis of care. Issue 5 (16th October 2019) - Roseira, J; Mão de Ferro, S; Moleiro, J; Currais, P; Lemos, J; Dionísio, J; Ferreira, S; Rosa, I; Lage, P; Szantho, A; Duro da Costa, J; Dias Pereira, A
SUMMARY: Primary esophageal cancer (EC) frequently presents as a locally advanced disease with airway involvement. Placement of combined esophageal and airway stents has been reported in small series to be an effective palliation strategy. Our aims are to present the largest cohort of EC patients who underwent double stent palliation and to evaluate the safety and efficacy of this approach. Longitudinal cohort study of patients with primary EC undergoing two-stage esophageal and airway stent placement at an oncology referral institute (January 2000–January 2019). Assessments: baseline demographics and clinical variables; baseline and week 2 dysphagia, dyspnea and performance status (PS) scores; baseline and week 8 body mass index (BMI); overall survival. Statistics: paired t -test; Kaplan–Meier method. Seventy patients (89% men, mean age 60.20 ± 8.41) underwent double stenting. Esophageal stent was placed for esophageal stenosis and dysphagia ( n = 41; placement of a second stent due to recurrence in nine cases) or esophagorespiratory fistulas (ERFs) ( n = 29); airway stent was required for ERF sealing ( n = 29 + 7 new ERFs after esophageal stent) and to ensure airway patency due to malignant stenosis ( n = 29; placement of a second stent due to recurrence in 13 cases) or compression ( n = 5). There were 13, endoscopically managed, major complications after esophageal stent [hemorrage ( n = 1), migration ( n = 5) and new fistulas ( n = 7)]. As for airway stents, four major complications were recorded [hemorrage ( n = 1) and three deaths due to respiratory infection and ultimately respiratory failure 3–7 days after the procedure]. Overall, patients showed significant improvement in dysphagia and dyspnea symptoms (3.21 vs. 1.31 e 15.56 vs. 10.87; P < 0.001). There was a PS improvement for 89.2% ( n = 58) of the patients. BMI at week 8 was comparable to baseline records. Mean survival was 137.83 ± 24.14 days (95% CI: 90.51–185.15). Survival was longer for better PS (PS1, 249.95 days; PS2, 83.74 days; PS3, 22.43 days; PS4, 30.00 days). This is the largest comprehensive assessment of double stent palliation in advanced incurable EC. For both esophageal or airway stenosis and fistula, placement of combined esophageal and airway stents was a feasible, effective, fast-acting and safe modality for symptom palliation and body mass maintenance. Patient autonomy followed symptom improvement. Since it is impossible to provide treatment for cure in most of these cases, this endoscopic strategy, performed in differentiated units with the required technical capacity, may guarantee treatment for the relief of palliative EC.